1996
DOI: 10.1111/j.1365-2362.1996.tb02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes in serum vitamin K1, triglyceride, cholesterol, osteocalcin and 25‐hydroxyvitamin D3 in patients after hip replacement for fractured neck of femur or osteoarthritis

Abstract: Serum vitamin K1 concentrations were measured at presentation (just before surgery) and then at weekly intervals for 3 weeks in two groups of elderly patients requiring either hemiarthroplasty for fractured neck of femur (FON, n = 13) or total hip replacement for osteoarthritis of the hip (OA, n = 16). In comparison with healthy elderly volunteers (n = 25), serum vitamin K1 concentrations were significantly lower in both groups at presentation, and fell significantly within 24 h after surgery to concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…The plasma phylloquinone concentrations in this British cohort were comparable to previous studies (Hart et al, 1985;Bitensky et al, 1988;Roberts et al, 1996). Studies in the USA have reported higher absolute phylloquinone levels in elderly compared to younger subjects (Sadowski et al, 1989;Sokoll & Sadowski, 1996).…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan supporting
confidence: 86%
See 1 more Smart Citation
“…The plasma phylloquinone concentrations in this British cohort were comparable to previous studies (Hart et al, 1985;Bitensky et al, 1988;Roberts et al, 1996). Studies in the USA have reported higher absolute phylloquinone levels in elderly compared to younger subjects (Sadowski et al, 1989;Sokoll & Sadowski, 1996).…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan supporting
confidence: 86%
“…To our knowledge, this is the first report of plasma phylloquinone concentrations in Chinese and African subjects. The high phylloquinone concentrations in the cohort of Chinese women from Shenyang where osteoporotic fractures are rare (Yan et al, 1999), is compatible with the association of low circulating phylloquinone with a high incidence of osteoporotic fracture in Britain and North America (Hart et al, 1985;Bitensky et al, 1988;Roberts et al, 1996;Booth et al, 2000). Plasma phylloquinone concentration is readily affected by dietary intake and rapidly raises blood concentrations, which then fall within a few hours (Suttie et al, 1988;Ferland et al, 1993;Sokoll et al, 1997;Booth et al, 1999).…”
Section: Ethnic Differences In Osteocalcin C-carboxylation Sr Beavan mentioning
confidence: 60%
“…Roberts et al (22) have reported that vitamin K concentration is low in osteoarthritis patients, but they have not mentioned the relationship between vitamin K concentration and cartilage metabolism. In this regard, this is the first study to consider this relationship in patients with bilateral K-OA.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 More recently these data were confirmed, 20 and it was found that plasma menaquinone concentrations were also substantially reduced in these patients. 21 Because it was not clear from these data whether the observed low circulating vitamin K levels were associated with a detectable vitamin K deficiency in bone tissue, Knapen et al developed an assay to assess the ratio between normal and undercarboxylated osteocalcin, and found that the fraction of undercarboxylated osteocalcin was increased in postmenopausal women.…”
Section: Vitamin K and Bonementioning
confidence: 78%